The reality of leadership behavior styles in the directorates of education in the governorates of Gaza from the point of view of their employees (Palestine Technical College Journal for Research and Studies, 2022)
The study aimed to identify the reality of leadership behavior styles in the directorates of education in the governorates of Gaza from the point of view of their employees. (Males and females) who work in the directorates of education in the governorates of Gaza, where the questionnaire was used as a tool for the study, and (300) questionnaires were distributed to the study sample, which were selected by the stratified random method, and (273) valid questionnaires were retrieved for analysis, with a recovery rate of (91%), The results of the study showed that the dominant leadership style in directorates of education in Gaza governorates is the democratic style, where it came in the first place with a relative weight (76.96%), i.e. to a high degree, followed by the autocratic style, where it came in second place with a relative weight (65.72%), i.e. in a medium degree, and finally the style came The anarchist ranked third and last, with a relative weight (51.44%), i.e. a low degree, The results also showed that there were no statistically significant differences between the average estimates of the sample members of the total degree of the dimensions of the leadership behavior axis in the directorates of education in the governorates of Gaza due to the variables (gender, academic qualification, years of service, directorate), while there were statistically significant differences between the average estimates of individuals The sample of the total degree of the dimensions of the leadership behavior axis dimensions in the directorates of education in the governorates of Gaza is due to the variable of the job title, In light of the results, the researcher recommended holding training courses for directors of education directorates to identify leadership styles in terms of advantages and disadvantages, and in which it is desirable to use a specific leadership style, and work within the directorates to take appropriate measures within the directorates to enhance the democratic style and reduce the behaviors of the autocratic and chaotic style, and activate the role of Social committees within the directorates by increasing communication and communication between senior management and workers through periodic meetings, recreational activities and social events.
Keywords: leadership behavior styles; education directorates